Hubungan Kausalitas antara Inflasi dan Pengangguran di Indonesia Tahun 2002 - 2021 - Kusumastuti, Ira; Sasana, Hadi (Jurusan PIPS FKIP UMMY Solok, 2022)
This study aims to examine the relationship between inflation and unemployment in Indonesia. The research data was taken from 2002-2021 from the World Bank (World Bank). The method used is Granger causality which previously performed the optimal lag test first. The results showed that unemployment had an effect on inflation. On the other hand, inflation has no effect on unemployment. This shows that the relationship between inflation and unemployment only occurs in one direction, namely from unemployment to inflation. Thus the trade off between inflation and unemployment occurs and inflation control must be implemented immediately.